Sparkes, Rev. North River. Photograph of man being ordaned in church. - Sparkes, Rev.
A photograph of Deacon John Sparkes in church being ordaned with a blue sash by Deacon Bell with Bishop Peddle standing to his left reciting something off a piece of paper. 6 people total in picture.